Challenges in teaching of renewable energies in a digital world during COVID-19: From face-to-face to remote learning in Colombia - Garzón Baquero, Jossie Esteban; Bellon Monsalve, Daniela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The COVID-19 pandemic-induced worldwide contingency has significantly disrupted the way education has been delivered, going through a crucial period of change and adaptation. But how does this dynamic impact both students’ and teachers’ educational process? This research on the teaching of renewable energies at the higher education level in engineering programs reveals the main challenges to this transformation as well as how they were overcome. The methodology is qualitative with two-way dynamic reflection, between the facts and their interpretation, and impacts 130 engineering students, from all of Colombia’s regions. Among the main results, six challenges stand out, which were addressed through different strategies.